From crisis to recovery: a case report and literature review of early extracorporeal membrane oxygenation and esophagogastroduodenoscopy intervention in a patient with extended-release bupropion overdose - Simpson, Matthew D.; Awuah, Kojo-Frimpong; Modugula, Sujith; Patel, Dhaval; Cheema, Tariq (International Journal of Research in Medical Sciences, 2024)
Drug poisoning, including bupropion overdose, presents significant clinical challenges with rising mortality rates. Extracorporeal membrane oxygenation (ECMO) has emerged as a potential therapeutic option, particularly in cases of cardiovascular collapse refractory to conventional treatment. However, the role of early ECMO initiation in bupropion intoxication remains under-explored. We present a case of a 41-year-old male with an extended-release bupropion overdose who developed cardiovascular collapse despite standard interventions. The patient underwent early initiation of ECMO and esophagogastroduodenoscopy for drug removal. Within 72-hours of ECMO initiation, the patient demonstrated significant hemodynamic improvement and was successfully weaned off vasopressors. The patient was extubated and transitioned to the medical floors with continued improvement. Early ECMO initiation may be beneficial in bupropion overdose cases presenting with cardiovascular collapse refractory to standard interventions. This case highlights the potential role of ECMO in managing severe bupropion intoxication and suggests further exploration of ECMO as an early intervention in drug poisoning cases.